Estrous Signs and Progesterone Profile of Ongole Grade Cows Synchronized at Different Ages Fed Different Level of Dietary Crude Protein - R. N. Hayati; Panjono Panjono; A. Irawan (Faculty of Animal Science, Bogor Agricultural University, 2021)
This study aimed to evaluate the effects of concentrate supplementation containing different protein levels on estrous signs and progesterone profiles of two age groups of Ongole Grade cow. Thirty females cows were grouped according to their ages (G1= 25±1.6 months; G2= 37±1.7 months), where each group received 3 dietary treatments with 5 replicates. The dietary treatment was based on CP levels of total mixed ration (TMR) (T1= 7.41% CP; T2= 8.23% CP; and T3= 9.17% CP). The cows were synchronized using PGF2α and GnRH, followed by time-fixed artificial insemination (TAI) using frozen semen. Data on nutrient intake and progesterone concentration were subjected to a randomized complete block design of ANOVA following a factorial arrangement of 2×3 while data of estrous signs were analyzed using non-parametric methods of Kruskal-Wallis and independent t-test. The results showed that there was a significant interaction effect between age group and dietary TMR treatment on CP intake and TDN intake in which the highest intakes were found in older cows (G2) fed TMR at 7.41% CP (T1) (p<0.01). Dry matter intake (DMI) was not affected either by age group or level of concentrate supplementation. Results also suggested that estrous signs, including vulva redness, swollen vulva, and mucus discharge, were higher in older cows (G2) than in younger cows (G1). In addition, interactions were also found on progesterone levels, whereas younger cows (G1) fed TMR with 9.17% CP (T3) showed the highest concentration of progesterone on d 5, 17, and 21 (p<0.01). In conclusion, this study suggests that younger cows receiving the highest CP diet (T3) result in higher progesterone concentration during the experimental period. Therefore, it is important to fed sufficient dietary CP especially for cattle in early reproduction period to optimize the reproductive performance.